Ludicity in (Glotto)Didactic – State of Research and Evolution of the Method (Ludicity in (Glotto)Didactic, 2020)
The article consists of two parts. The first one presents previous research on ludicity in teaching inter alia foreign languages. It shows merits and drawbacks of using the ludic methods, which is going to be more and more popular in contemporary didactic. The second part contains descriptions of particular articles included in the volume and thereby helps to learn what the publication contains.